THE RELATIONSHIP BETWEEN DIGITAL LITERACY AND DIGITAL MARKETING CREATIVITY IN STUDENTS AT SMK MASTER INDONESIA - Murdiyono Murdiyono; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana (Nusantara Hasana Journal, 2023)
This study aims to analyze the relationship between digital literacy and digital marketing creativity among students at SMK Master Indonesia. Digital literacy is a crucial skill for students in effectively utilizing information technology and social media for digital marketing activities. The research method used a quantitative approach by distributing questionnaires to SMK Master Indonesia students as research respondents. The results showed that digital literacy has a positive relationship with students' digital marketing creativity, particularly in the ability to create promotional content, use social media, and digital technology-based marketing innovation